Prevalence of hepatitis C virus infection among recyclable waste collectors in Central-West Brazil - Thais Augusto Marinho; Carmen Luci Rodrigues Lopes; Sheila Araujo Teles; Nadia Rubia Silva Reis; Megmar Aparecida dos Santos Carneiro; Andreia Alves de Andrade; Regina Maria Bringel Martins (Memorias do Instituto Oswaldo Cruz, 2013)
The prevalence of hepatitis C virus (HCV) in a population of recyclable waste collectors (n = 431) was assessed using a cross-sectional survey in all 15 cooperatives in the city of Goiânia, Central-West Brazil. The HCV prevalence was 1.6% (95% confidence interval: 0.6-3.6) and a history of sexually transmitted infections was independently associated with this infection. HCV RNA (corresponding to genotype 1; subtypes 1a and 1b) was detected in five/seven anti-HCV-positive samples. Although the study population reported a high rate (47.3%) of sharps and needle accidents, HCV infection was not more frequent in recyclable waste collectors than in the general Brazilian population.